Research on the cross-contagion between international stock markets and geopolitical risks: the two-layer network perspective - Xiao-Li Gong; Hao-Yang Ning; Xiong Xiong (Financial Innovation)
Abstract As the international environment changes, frequent geopolitical crises continue to hinder the healthy development of global stock markets. To analyze in-depth the risk contagion path between the international stock market and geopolitics under the impact of extreme events, this paper explores the tail risk interactive contagion mechanism and dynamic effects of the double-layer network between the international stock market and geopolitics from the perspective of complex networks. Empirical research finds that geopolitical conflicts exacerbate risk contagion among international stock markets, and there are significant differences in risk contagion between developed and emerging economies. The analysis of the complex interaction effect in the double-layer network of the international stock market and geopolitics shows that the intralayer risk spillover effect of geopolitics in the short term is significantly higher than that of the stock price volatility network layer. Finally, the study on the dynamic changes of the double-layer network connectedness between the international stock market and geopolitics found that the shock of extreme events, such as military conflict and public health security, is an important factor in triggering the cross-contagion of risks. The research conclusions provide new ideas for preventing the cross-contagion of geopolitical risks in the stock markets of various countries under the evolution of the global political and economic pattern.